Extracurricular Students’ Activity as a Component of Their Professional Training - Zagnybida, Raisa (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article highlights the importance of professional training of would-be service industry experts. It has been proved that curriculum plays an important role in training students for their future career although professional training efficiency depends greatly on a system of extracurricular activities at the institution of higher learning. In the research context the essence of the term «extracurricular activities» has been defined more precisely; extracurricular activities as a component of interrelated work of educational institutions has also been studied, which is an integral part of professional training and is accomplished beyond the syllabus in order to create conditions for students’ individual progress and their self-realization. The emphasis is made on the following main tasks which must be solved in the process of designing a would-be service industry expert during extracurricular activities: teach the students to define the level of their professional self-improvement at circumstances of higher educational establishment; improve the ability to independently choose means, methods and main directions of professional self-improvement; design skills to find guidelines, which must be reached in individual professional development; improve skills to independently study and analyze hospitality industry etc. The main kinds of extracurricular activities are considered to be the following: individual work, research work, educational training, and leisure activities.